Recent Advances in Palladium-Catalyzed C(sp3)–H Activation for the Formation of Carbon–Carbon and Carbon–Heteroatom Bonds - Dastbaravardeh, Navid; Christakakou, Maria; Haider, Maximilian; Schnürch, Michael (Synthesis, 2014)
Within this review, recent developments in the field of C(sp3)–H activation catalyzed by palladium are discussed. Both intra- and intermolecular reactions towards carbon–carbon and carbon–heteroatom bonds are covered. In the case of intramolecular reactions, asymmetric versions are reported as well. The main focus of this review is literature of the last five years until late 2013. 1 Introduction2 Intramolecular C(sp3)–H Activation2.1 Carbon–Carbon Coupling2.2 Carbon–Heteroatom Coupling2.3 Stereoselective Reactions 3 Intermolecular C(sp3)–H Activation3.1 Carbon–Carbon Coupling3.2 Carbon–Heteroatom Coupling4 Conclusion and Outlook
Keywords: alkylation; arylation; palladacycles; homogeneous catalysis; organometallic reagents